The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/mats.202000090
|View full text |Cite
|
Sign up to set email alerts
|

End‐Pulled Translocation of a Star Polymer Out of a Confining Cylindrical Cavity

Abstract: dispersant, potential drug delivery agents, thermoplastic elastomers, surfactants, and lubricants. [2,3,5] In addition, more recently, there is an increased interest in the biomedical field for using star-shaped macromolecules as drug release carriers by immobilizing biologically active molecules on their arms. [6-8] Polymer translocation through a nanopore is a fundamental process in diverse biological systems, including DNA and RNA translocation across nuclear pores, protein transport through membrane channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The first theoretical study of pulled polymer translocation was performed by Kantor and Kardar [ 55 ], predicting for moderate pulling forces. This was followed by a number of theoretical and numerical studies reporting the scaling behavior under different force regimes as well as different states of polymer [ 81 , 82 , 83 , 84 , 85 , 86 ]. The scaling exponents for various models, for both unbiased and driven translocation, are tabulated by Palyulin et al in their review article [ 21 ].…”
Section: Polymer Translocation: Highlights From Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The first theoretical study of pulled polymer translocation was performed by Kantor and Kardar [ 55 ], predicting for moderate pulling forces. This was followed by a number of theoretical and numerical studies reporting the scaling behavior under different force regimes as well as different states of polymer [ 81 , 82 , 83 , 84 , 85 , 86 ]. The scaling exponents for various models, for both unbiased and driven translocation, are tabulated by Palyulin et al in their review article [ 21 ].…”
Section: Polymer Translocation: Highlights From Theoretical Developmentmentioning
confidence: 99%
“…Chen et al [ 95 ] studied the pulled translocation of a compact globule and it was shown that the translocation could be controlled by changing the monomer–monomer interaction. Tilahun et al simulated the pulled translocation of a star polymer and studied the dependence of on the chain functionality and mass, as well as on the magnitude of the pulling force [ 86 ]. Another approach, based on the same principle as pulled translocation but less explored, involves immobilizing the DNA strand by tethering it to a bead or a probe.…”
Section: Controlling the Speed Of Translocationmentioning
confidence: 99%